1995
DOI: 10.1177/088626095010003008
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Emotional Correlates of Self-Reported Antigay Behaviors

Abstract: This study examined the relationship between the emotional response of homophobia and selected personality and self-report behavioral variables. Scales 4, 5, and 9 of the Minnesota Multiphasic Personality Inventory were related to the affective components of homophobia as measured by the Index of Attitudes Towards Homosexuals (IAH; formerly Index of Homophobia-Modified) and self-report of past aggressive behavior toward homosexuals as measured by a Self-Report of Behavior Scale (SBS), specifically developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 23 publications
11
45
0
Order By: Relevance
“…Bernat et al, 2001;Parrott and Zeichner, 2005;Patel et al, 1995]. The present results are consistent with these studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bernat et al, 2001;Parrott and Zeichner, 2005;Patel et al, 1995]. The present results are consistent with these studies.…”
Section: Discussionsupporting
confidence: 93%
“…Survey-based studies have demonstrated a positive association between sexual prejudice and self-reported past aggressive behavior toward gay men [Franklin, 2000;Patel et al, 1995;Roderick et al, 1998]. Laboratory-based studies have shown that sexually prejudiced men displayed higher levels of aggressive behavior toward a gay male, relative to the heterosexual male, but only after exposure to sexual violations of the traditional male gender role (i.e.…”
Section: Theories Of Antigay Aggressionmentioning
confidence: 99%
“…Research suggests that sexual prejudice is positively associated with antigay behaviors (Haddock & Zanna, 1998;Patel, Long, McCammon, & Wuensch, 1995;Roderick, McCammon, Long, & Allred, 1998;Van de Ven, Bornholt, & Bailey, 1996), negative affect (Mahaffey, Bryan, & Hutchinson, 2005a, 2005b, and anger (Ernulf & Innala, 1987;Van de Ven et al, 1996) in response to homosexuality. Additionally, two laboratorybased studies have demonstrated that after being exposed to male homosexuality, sexually prejudiced men experienced enhanced levels of anger and evinced more physical aggression toward a gay, relative to a heterosexual, male target (Bernat, Calhoun, Adams, & Zeichner, 2001;Parrott & Zeichner, 2005).…”
Section: Determinants Of Antigay Violencementioning
confidence: 99%
“…Specifically, numerous studies indicate that male sexual prejudice is strongly associated with rigid adherence to traditional male gender roles (Kilianski, 2003;Parrott, Adams, & Zeichner, 2002;Patel et al, 1995;Polimeni, Hardie, & Buzwell, 2000;Sinn, 1997;Stark, 1991). As such, it is posited that overt violations of the male gender role (e.g., homosexuality) represent a significant threat to the self-concept of men who endorse an extreme male gender role orientation (Herek, 1986(Herek, , 1988Whitley & Kite, 1998).…”
Section: Determinants Of Antigay Violencementioning
confidence: 99%
“…To this end, research indicates that endorsement of traditional male gender role beliefs predicts increased anger and aggression toward gay, but not heterosexual, men (Parrott and Zeichner 2008). Similarly, experimental and correlational studies have demonstrated that heterosexual men's self-reported sexual prejudice predicts increased anger and bias-motivated aggression toward gay men (Bernat et al 2001;Franklin 2000;Parrott and Zeichner 2005;Patel et al 1995;Roderick et al 1998). These studies suggest that men who endorse traditional beliefs about the male gender role and higher levels of sexual prejudice are particularly likely to express anti-gay anger and aggression.…”
Section: Introductionmentioning
confidence: 99%